Total knee revision arthroplasty: comparison between tibial tubercle osteotomy and quadriceps snip approach. Complication rate. - Di Benedetto, Paolo; Buttironi, Michele; Giardini, Piero; Mancuso, Francesco; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The total knee arthroplasty (TKA) revision is not a second timeof primary implant surgery but is a very complex issue for orthopedic surgeon. When local conditions makenecessary a greater visualization, medial para-patellar access with quadriceps snip (QS) or the osteotomy of thetibial tuberosity (TTO) can be the solutions. This work aims to compare the quadriceps snip and the detachmentof the tibial tubercle, focusing on possible complications. Materials and Methods: At our institution,between January 2017 and February 2019 52 TKA revision for periprosthetic joint infection (PJI) or asepticmobilization were performed. In 43 cases an extensive surgical approach was required: for patients with rangeof movement (ROM) < 60° was chosen TTO, while with ROM > 60° a QS was performed. Clinical and radiologicalfollow-up was available for all the 43 cases. Results: The data about clinical outcome in our study showthat both groups have a positive trend in KSS score over time with similar ROM results. Two partial avulsionsof patellar tendon during revision surgery were reported. Clinical outcome in both groups has shown goodresults at the end of follow-up with no post-operative incidence of complications. Conclusion: We can assertthat both QS and TTO are good approach for TKA revision. Future studies will be needed to understand ifpreparatory ROM is a good way to decide which surgical approach to use.(www.actabiomedica.it)